Prevalence, Comorbid Associations and Prognostic Value of the Hyperdense Middle Cerebral Artery Sign. (28th April 2013) - Aouad, Patrick; Hughes, Andrew; Valecha, Nishant; Gawarikar, Yash; Ahmad, Kate; O'Neil, Ross; Guduguntla, Murali; Lueck, Christian
Abstract : Background. The significance of the Hyperdense Middle Cerebral Artery Sign (HMCAS) is uncertain. Aims. This prospective study investigated the sensitivity, specificity, prevalence, prognosis, interobserver variability, and associated clinical features of HMCAS in acute ischemic stroke. Methods. Initial CT scans of 117 patients with acute ischemic stroke or transient ischemic attack (TIA) and 65 age-matched controls were reported independently by two neuroradiologists blinded to diagnosis. Details of initial stroke severity and comorbidities were collected, and outcome on the modified Rankin scale (mRS) was assessed at 3–6 months. Results. HMCAS was seen in 15% of all ischemic strokes and 25% of all middle cerebral artery (MCA) strokes; specificity was 100%. HMCAS was associated with more severe initial deficit and atrial fibrillation. Only 21% of patients with a first-ever MCA stroke and HMCAS had a good outcome (mRS ≤ 2 ) compared to 55% of those without the sign (P < 0.001 ). Interobserver agreement was only 0.747 (Kappa statistic). Conclusion. The prevalence, specificity, sensitivity, and clinical associations of HMCAS were similar to previous reports. This study confirmed prospectively that HMCAS was associated with a poorer outcome at 3 to 6 months and demonstrated interobserver variability in detection of the sign.